Alternate Strategies for Managing Resistance to Antibiotics and Pesticides - Amit Batabyal; Peter Nijkamp (European Regional Science Association (ERSA), 2005)
How should one manage the problem of resistance to antibiotics and pesticides? Although the salience of this question has now been recognized, the formal modeling of this question is very much in its infancy. Consequently, we have three objectives in this paper. First, we construct a dynamic and stochastic model of antibiotic or pesticide use. Second, we analyze two different strategies (interventionist and non-interventionist) for overseeing the problem of resistance. Finally, we identify a specific probability function and we show that whether the problem of resistance is best addressed with an interventionist strategy or a non-interventionist strategy depends fundamentally on this probability function.
Keywords: 330